The science and technology of rubber - Mark, James E., 1934-; Erman, Burak; Roland, Mike (Elsevier Academic Press, 2013)
The 4th edition of The Science and Technology of Rubber provides a broad survey of elastomers with special emphasis on materials with a rubber-like elasticity. As in the 3rd edition, the emphasis remains on a unified treatment of the material; exploring topics from the chemical aspects such as elastomer synthesis and curing, through recent theoretical developments and characterization of equilibrium and dynamic properties, to the final applications of rubber, including tire engineering and manufacturing. Many advances have been made in polymer and elastomers research over the past ten years since the 3rd edition was published. Updated material stresses the continuous relationship between the ongoing research in synthesis, physics, structure, and mechanics of rubber technology and industrial applications. Special attention is paid to recent advances in rubber-like elasticity theory and new processing techniques for elastomers. This new edition is comprised of 20% new material, including a new chapter on environmental issues and tire recycling. Provides the most comprehensive survey of elastomers for engineers and researchers in a unified treatment: the text moves from the chemical aspects such as elastomer synthesis and curing, through recent theoretical developments and characterization of equilibrium and dynamic properties, to the final applications of rubber, including tire engineering and manufacturing. Contains important updates to several chapters, including elastomer synthesis, characterization, viscoelastic behavior, rheology, reinforcement, tire engineering, and recyclingIncludes a new chapter on the burgeoning field of bioelastomers.